Enforceability of Environmental Rights: a Possible Panacea to Man's Environmental Imbroglio - Nigeria's Niger-Delta as a case Study - Oluwamuyiwa Ojo, Olayinka (Afrika Focus, 2020)
This research examines the potential of a human rights-based approach to address the environmental problems affecting Nigeria’s Niger Delta and the world at large. This research critically assesses the various environmental legislation and policies in Nigeria, and interrogates why, despite the enactment of an environmental provision in Section 20 of the Constitution, gross environmental injustice has occurred in the country. Further discussion on the methods and strategies that can be used to guarantee access to the Court, as well as enforcing the right to a healthy environment in Nigeria, despite the current provision of the Constitution, are elucidated. This research argues that a constitutionally enforceable right to a healthy environment, a full implementation of the African Charter on Human and Peoples’ Rights, the establishment of Environmental Courts and Tribunals (ECT), comprehensive and quantitative environmental citizen education, as well as the empowerment of environmental NGOs, may be the solution to the environmental challenges currently faced in Nigeria’s Niger Delta as well as the entire country. KEY WORDS: HUMAN RIGHTS, ENVIRONMENT LAW, SUSTAINABLE ENVIRONMENT, CONSTITUTION, ENFORCEMENT, EXTRATERRITORIAL, INTERNATIONAL LAW, CONVENTION